2015
DOI: 10.1093/schbul/sbv024
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging and the Prediction of Outcome in First-Episode Schizophrenia: A Review of Current Evidence and Directions for Future Research

Abstract: Neuroimaging data, possibly in combination with other biomarkers of disease, could help stratifying patients with psychoses to generate patient clusters clinically meaningful, and useful to detect true therapeutic effects in clinical trials. Optimization of Treatment and Management of Schizophrenia in Europe (OPTiMiSE), a large multicenter study funded by the FP7 European Commission, could generate these much-needed findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
53
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 50 publications
1
53
1
2
Order By: Relevance
“…Some of these neuroanatomical abnormalities are already evident in the so‐called at‐risk mental state (ARMS) for psychosis (Dazzan et al., ), including GM volume reductions of prefrontal (Cannon, ; Smieskova et al., ), temporal (Fusar‐Poli et al., ; Smieskova et al., ) and cingulate cortices (Fusar‐Poli, McGuire, et al., ; Fusar‐Poli et al., ; Smieskova et al., ), parahippocampal gyrus and hippocampus (Fusar‐Poli, McGuire, et al., ; Thermenos et al., ), insula and caudate (Smieskova et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these neuroanatomical abnormalities are already evident in the so‐called at‐risk mental state (ARMS) for psychosis (Dazzan et al., ), including GM volume reductions of prefrontal (Cannon, ; Smieskova et al., ), temporal (Fusar‐Poli et al., ; Smieskova et al., ) and cingulate cortices (Fusar‐Poli, McGuire, et al., ; Fusar‐Poli et al., ; Smieskova et al., ), parahippocampal gyrus and hippocampus (Fusar‐Poli, McGuire, et al., ; Thermenos et al., ), insula and caudate (Smieskova et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Predictive biomarkers are widely used to influence the treatment selection for a variety of diseases, namely cancer, but even in the assessment of experimental thermal pain (Wager et al, 2013). Dazzan et al concluded that alterations of gray and white matter identified on structural neuroimaging, predominantly distributed in the medial temporal and prefrontal cortices, are potential neuroanatomical markers for the prediction of poor symptomatic and functional outcome (Dazzan et al, 2015). There have also been studies that identified correlations between structural features and antipsychotic treatment response from the perspectives of both volume and morphology, involving asymmetry and hypogyria (Altamura et al, 2017;Dusi et al, 2017;Francis et al, 2018;Fung et al, 2014;Hutcheson, Clark, Bolding, White, & Lahti, 2014;Molina, Taboada, Aragues, Hernandez, & Sanz-Fuentenebro, 2014;Morch-Johnsen et al, 2015;Palaniyappan et al, 2013;Premkumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Finding predictors of response to antipsychotic drug treatment is of critical importance to improving outcomes for psychotic disorders [1,2]. A priori identification of patients who are not likely to respond to a specific treatment strategy could reduce the number and length of ineffective treatment trials.…”
Section: Introductionmentioning
confidence: 99%